The correlation between the use of ondansetron and mortality in sepsis associated encephalopathy patients: a retrospective ICU cohort study - Yang, Shuo; Wei, Yi-Qu; Liu, Ya-Zhou; Wang, Xiao-Lin; Gao, Jin-Xia (Frontiers in Pharmacology, 2025)
BackgroundSepsis-associated encephalopathy (SAE) is a severe complication with high mortality. The effect of ondansetron (OND) on the outcomes of SAE patients remains unclear.MethodsUsing the Intensive Care IV Medical Information Mart (MIMIC-IV) database, we identified 7,829 SAE patients, comprising an OND group (n = 3,954) and a non-OND group (n = 3,875). Propensity score matching (PSM) was employed to generate 3,066 pairs of matches in a 1:1 ratio. The primary outcomes encompassed the 30-day, 90-day, 180-day, and 360-day mortality rates. The secondary outcomes included the duration of ICU stay, the duration of mechanical ventilation, and the incidence of QT interval prolongation. Survival analysis was conducted using Cox proportional hazards regression and Kaplan-Meier curves. Sensitivity analyses, including E-value assessment and a landmark analysis at 5 days to address immortal time bias, were performed. Subgroup analysis was applied to investigate potential differences in the effect of OND treatment on clinical outcomes among various subgroups.ResultFollowing PSM, the baseline characteristics were well-balanced between the cohorts. The group receiving OND demonstrated significantly lower mortality rates at 30 days (HR = 0.64, 95% CI [0.56–0.73], *p*<0.001), 90 days (HR = 0.75, 95% CI [0.66–0.84], *p*<0.001), 180 days (HR = 0.78, 95% CI [0.69–0.88], *p*<0.001), and 360 days (HR = 0.76, 95% CI [0.67–0.85], *p*<0.001) compared with the non-OND group. The landmark sensitivity analysis confirmed the robustness of this survival benefit (p < 0.001). Kaplan-Meier analysis confirmed a significant survival advantage for OND-treated patients with SAE. After matching, the OND group was associated with significantly shorter durations of ICU stay and mechanical ventilation compared with the non-OND group; however, the incidence of QT interval prolongation did not differ significantly between the two groups. Subgroup analysis indicated that adult patients younger than 65 years may derive greater survival benefit from OND treatment.ConclusionIn SAE patients, OND use is associated with significantly lower short- and long-term mortality, suggesting its potential as an adjunct therapy. However, further prospective randomized controlled trials are warranted to validate these results.